ANALISIS KOMITMEN KERJA GURU TK DI KECAMATAN SULIKI KABUPATEN LIMA PULUH KOTA SUMATERA BARAT - Lestari, Widia; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : The author formulates in this research how is the work commitment of kindergarten teachers in Suliki sub-district, Lima Puluh Kota, West Sumatra? This research was conducted in Kindergarten, Suliki Sub-District, Lima Puluh Kota Regency, West Sumatra in May 2019. This research is a one-way descriptive research that is research that tries to tell the current problem solving based on data, and also presents data, analyzes and interpret. The subjects in this study were all kindergarten teachers in Suliki Sub-District, Lima Puluh Kota Regency, West Sumatra, totaling 18 people. Based on the results of the study, it can be concluded that the work commitment of kindergarten teachers in Suliki Sub-District, Lima Puluh Kota Regency, West Sumatra, obtained a percentage of 74.34% with a good category. That is, teachers who teach in kindergartens in Suliki sub-district, Lima Puluh Kota Regency, West Sumatra have the emotional attitude of a teacher and are involved in all school affairs, they also have a high commitment to survive because of the awareness to teach, and have a normative feeling that is maintaining the existence of the school with their existence . Key Words: Work Commitment